Photodecomposition of iodinated contrast media and subsequent formation of toxic iodinated moieties during final disinfection with chlorinated oxidants - Allard, Sebastien; Criquet, J.; Prunier, A.; Falantin, C.; Le Person, A.; Yat-Man Tang, J.; Croué, J. (IWA Publishing, 2016)
Large amount of iodinated contrast media (ICM) are found in natural waters (up to µg.L-1 levels) due to their worldwide use in medical imaging and their poor removal by conventional wastewater treatment. Synthetic water samples containing different ICM and natural organic matter (NOM) extracts were subjected to UV254 irradiation followed by the addition of chlorine (HOCl) or chloramine (NH2Cl) to simulate final disinfection. In this study, two new quantum yields were determined for diatrizoic acid (0.071 mol.Einstein-1) and iotalamic acid (0.038 mol.Einstein-1) while values for iopromide (IOP) (0.039 mol.Einstein-1), iopamidol (0.034 mol.Einstein-1) and iohexol (0.041 mol.Einstein-1) were consistent with published data. The photodegradation of IOP led to an increasing release of iodide with increasing UV doses. Iodide is oxidized to hypoiodous acid (HOI) either by HOCl or NH2Cl. In presence of NOM, the addition of oxidant increased the formation of iodinated disinfection by-products (I-DBPs). On one hand, when the concentration of HOCl was increased, the formation of I-DBPs decreased since HOI was converted to iodate. On the other hand, when NH2Cl was used the formation of I-DBPs was constant for all concentration since HOI reacted only with NOM to form I-DBPs. Increasing the NOM concentration has two effects, it decreased the photodegradation of IOP by screening effect but it increased the number of reactive sites available for reaction with HOI.For experiments carried out with HOCl, increasing the NOM concentration led to a lower formation of I-DBPs since less IOP are photodegraded and iodate are formed. For NH2Cl the lower photodegradation of IOP is compensated by the higher amount of NOM reactive sites, therefore, I-DBPs concentrations were constant for all NOM concentrations. 7 different NOM extracts were tested and almost no differences in IOP degradation and I-DBPs formation was observed. Similar behaviour was observed for the 5 ICM tested. Both oxidant poorly degraded the ICM and a higher formation of I-DBPs was observed for the chloramination experiments compared to the chlorination experiment. Results from toxicity testing showed that the photodegradation products of IOP are toxic and confirmed that the formation of I-DBPs leads to higher toxicity. Therefore, for the experiment with HOCl where iodate are formed the toxicity was lower than for the experiments with NH2Cl where a high formation of I-DBPs was observed.